Anthropology between academic and instrumental: (Analytical- critical study of the nature of the relationship between anthropology and colonialism) - Fayad, Hossam Aldin Mahmoud (Journal of Humanities & Social Sciences, 2021)
The research aimed to clarify the concept of anthropology, explain the factors and causes of its emergence as a science that studies primitive societies, and analyzes and critiques the nature of the correlation between them and colonialism. It also sought to study the effect of instrumental rationalism on the whole of anthropological studies. The research relied on the critical analytical method in its study of the subject of the study. The research also reached a set of results, the most important of which is the existence of a correlation between the emergence of anthropology as an academic discipline concerned with the study of primitive societies and the concept of expansionist European colonialism. In addition to that anthropology had an important role in understanding the developments that humankind experienced, but the findings of anthropology were not used in the service of mankind, but rather remained locked in the offices of the colonial authority and its followers in order to exploit them to control developing societies. In the end, the research recommended the necessity to formulate an ethical charter to guide the paths of anthropological studies in a way that does not conflict with the human goals and objectives for which they were found. And activating the role of anthropology departments in Arab and Islamic universities on the basis of linking the university to society to prepare studies and research on the problems and issues that these societies suffer in proportion to their specificity so as not to deviate from their historical context in employing their results objectively.